Physicochemical, Antioxidant and Sensory Attributes of Steamed Bun (Mantao) with Dried Figs Puree - Karim, Siti Nabilah; Abdul Rahim, Assoc. Prof. Dr. Alina (Journal of Quranic Sciences and Research, 2021)
Bakery products have increased in demand but majority of them have low fiber content. According to Ibn Seereen, a scholar in the science of dreams, figs, denote wealth and prosperity. Dried figs are found to be a good source of nutritional composition especially in phenolic compound and fiber content. The aim of this experiment is to study the effect on steamed bun incorporated with dried figs puree in terms of physicochemical properties, antioxidant activity and sensory acceptability. Dried fig was used as puree to incorporate with wheat flour in steamed bun formulations at different levels (0 %, 2 %, 5 % and 10 %). The effect of dried figs puree incorporation on quality attributes include proximate composition, antioxidant, physical property such as color were analyzed and compared to a control steamed bun (0 %). Total phenolic content and antioxidant activity of steamed buns were measured with a spectrophotometer using light with a wavelength of 760 nm and 517 nm respectively. It was found that the incorporation of dried figs pure in steamed buns gave no significant different (P>0.05) of ash, moisture, protein and crude fiber content when compared to control. Steamed bun with 10 % of dried figs had significantly darker color (P<0.05) differences for puree compared to control. The highest values for total phenolic compound and the radical scavenging activity were obtained in T3 (10 %) which are 0.98 mg GAE/g and 76.73 % respectively. Overall results show no significant different (P>0.05) of steamed bun from all formulations in sensory evaluation indicating the consumers acceptability towards steamed bun incorporated with dried figs puree along with the nutritional advantages imparted from it. In short, the importance of healthy balanced diet can be understood in the Quran and Sunnah of Holy Prophet (PBUH).